Práticas de gamificação em programas de slides para a potencialização do letramento crítico nas aulas de língua portuguesa no ensino médio - Alves, Emiliane Cristina Cruz Matias (2023)
Due to the transformations of mass communication and the advances in technology, the meaningful changes in the society provide quickly the access to information and it demands a school education from the population that enables them to become more active and capable of criticizing the political and social problems presented to them. That way, the use of more interactive and lucid methodologies, such as digital games, is being consider in order to verify the practical contributions of gamification as a strategy to enhance the critical literacy of students in Portuguese language classes. In this approach, we developed a game, in a slide presentation program, to be applied in high school classes, with situations that proposed discussions and debates, aiming to observe whether this dynamic helps in the learning and in the reflexive, critical, and engaged decision making of the students when facing texts that bring up social problems. To reach this goal, we initially started from the theories of new literacies and critical literacy (DUBOC, 2016; KLEIMAN, 1995; SOARES, 2004, 2009; STREET, 2014), and we proceed to the theoretical bases which study the process of gamification and the use of digital games in teaching practice (PRENSKY, 2012; GEE, 2009; MATTAR, 2010; HUIZINGA, 2014). In terms of methodology, we have the qualitative model, since the results acquired are of a subjective nature; moreover, we can also find in this research methodological characteristics of a research-action, since it presents itself as a continuous, empirical and systematic attempt based on improving the practice (TRIPP, 2005). According to the observations made during the application of the game, we realized that the format of this activity promotes a greater interest and motivation of learners to share their ideas with everyone in the class, spontaneously and without apprehension, revealing themselves as an agent belonging and important to a society full of issues to be discussed and solved. And this could be proven both in the good participation during the application of the game, as well as in the words of the participants and their answers in the evaluative survey at the end of the activity.